2020
DOI: 10.1111/aphw.12215
|View full text |Cite
|
Sign up to set email alerts
|

The Moderator Role of Passion for Work in the Association between Work Stressors and Secondary Traumatic Stress: A Cross‐Level Diary Study among Health Professionals of Intensive Care Units

Abstract: Background: Secondary traumatic stress (STS), a construct formed by compassion fatigue, shattered assumptions, and symptomatology, has been scarcely studied in intensive care units (ICU). In these units, healthcare workers encounter daily work stressors which impact on their health and well-being. Also, previous literature revealed a passion for caring among these workers, finding two types: harmonious passion, which may protect them against negative outcomes, and obsessive passion, which may boost negative co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 52 publications
5
13
0
Order By: Relevance
“…In fact, these statements could be an explanation of the high levels of harmonious passion maintained over time in the two waves, as a positive and stable resource to keep optimum levels of well-being. Looking closely, previous findings revealed that this harmonious passion prevents compassion fatigue, as the emotional fatigue related to STS [ 25 ], that implies the effect of this passion in the emotional component. Linked to that, these findings reveal as well how this harmonious passion could change the relationship of the professional with the job demands, as previous authors confirmed [ 43 ].…”
Section: Discussionsupporting
confidence: 58%
See 3 more Smart Citations
“…In fact, these statements could be an explanation of the high levels of harmonious passion maintained over time in the two waves, as a positive and stable resource to keep optimum levels of well-being. Looking closely, previous findings revealed that this harmonious passion prevents compassion fatigue, as the emotional fatigue related to STS [ 25 ], that implies the effect of this passion in the emotional component. Linked to that, these findings reveal as well how this harmonious passion could change the relationship of the professional with the job demands, as previous authors confirmed [ 43 ].…”
Section: Discussionsupporting
confidence: 58%
“…No interaction effect was found concerning STS, thus, we need to continue improving the variables studied to check those resources with greater impact. This means that harmonious passion cannot particularly protect employees that are confronted with high job demands during the pandemic, and previous studies have found this protector role when job demands are high if we consider the cognitive changes of the trauma, that is, shattered assumptions [ 25 ]. Possibly, harmoniously passionate workers are able to see less overload and more job control during their working times [ 43 ], but the excessive increase of job demands during this pandemic makes it difficult to moderate this relationship.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…If we consider HP and OP to be resources in the context of COR, the next step is to appraise how they impact stress. Previous research in health-care settings has found both a negative (Bélanger et al , 2015; Moreno-Jiménez et al , 2021) and null relationship (Moreno-Jiménez et al , 2020) of HP with various forms of stress, whereas OP has consistently shown a positive relationship with stress (Bélanger et al , 2015; Moreno-Jiménez et al , 2020). More broadly, meta-analysis found a negative correlation for work-related HP ( k = 3, N = 630, ρ = −0.44; 80% credibility interval (CI) [−0.49, −0.38]) and a positive correlation for work-related OP ( k = 3, N = 630, ρ = 0.14; 80% CI [0.04, 0.24]) with psychological distress (Pollack et al , 2020).…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 92%